Drug Treatment as HIV Prevention Among Women and Girls Who Inject Drugs From a Global Perspective: Progress, Gaps, and Future Directions. (1st June 2015) - Springer, Sandra A.; Larney, Sarah; Alam-mehrjerdi, Zahra; Altice, Frederick L.; Metzger, David; Shoptaw, Steven
Abstract : Abstract: Although there have been significant reductions in the number of new HIV infections globally from 2009 to 2013, incidence remains unacceptably high for persons who use drugs. In many settings, women and girls who inject drugs (WWID) with HIV/AIDS experience poor treatment access, including evidence-based practices like antiretroviral therapy and drug treatment. Medication-assisted therapies (MAT) for substance use disorders are especially inaccessible, which in their absence, increases HIV transmission risk. Irrespective of setting or culture, drug treatment using MAT is not only effective but also cost-effective at reducing opioid use and linked injection and sexual risks. Data presented here for WWID address their access to MAT for opioid addiction and to treatments being developed that address the relationship, family, and vocational needs of this group. The most glaring finding is that globally, WWID frequently are excluded in surveys or studies with an impressive lack of disaggregated data by gender when surveying access to MAT—even in wealthy countries. Despite this, there have been some striking improvements in implementing drug treatment as prevention, notably in Iran and China. Still, real barriers remain for women and girls to accessing drug treatment, other harm reduction services, and antiretroviral therapy. Development and/or implementation of interventions that facilitate women and girls engaging in drug treatment that address their roles within society, work, and family/relationships, and outcome evaluation of these interventions are crucial.